Circulating tumour DNA, a promising biomarker for the management of colorectal cancer. (February 2018) - Khakoo, Shelize; Georgiou, Alexandros; Gerlinger, Marco; Cunningham, David; Starling, Naureen
Highlights: ctDNA is detectable in CRC patients with localised and metastatic disease. ctDNA may be a biomarker of minimal residual disease after curative surgery. In localised rectal cancer ctDNA may facilitate adaptive therapy approaches. In metastatic disease ctDNA is predictive of treatment response or failure. Standardisation of ctDNA detection and interpretation is needed before clinical use. Abstract: Circulating cell free tumour DNA (ctDNA) maintains the same genomic alterations that are present in the corresponding tumour, thereby allowing for quantitative and qualitative real-time evaluation in body fluids as an alternative to onerous repeat biopsies. Improvements in the sensitivity of techniques used to identify ctDNA has led to a surge of research investigating its role in the detection of: early disease, relapse, response to therapy and emerging drug resistance mechanisms. Following curative surgery, ctDNA detection is a promising marker of minimal residual disease and could better select patients for adjuvant chemotherapy. Longitudinal monitoring could help identify early relapse. In metastatic disease, ctDNA can predict response to chemotherapy prior to evidence of disease progression on imaging and investigate novel primary and acquired resistance mechanisms to targeted therapies. More experience in detecting, analysing and interpreting ctDNA within prospective trials, will better define its role for implementation into routine clinical practice.